A Fortunate Story of an Unusual AK-47 Bullet Trajectory: Always Keep a Smartphone in Your Pocket. Issue 3 (18th April 2016) - Thabouillot, Oscar; Perrier, Pierre; Roche, Nicolas-Charles; Agard, David; Barbier, Olivier; Martin, Guillaume; Viant, Eric; Leclere, Jean-Baptiste
Abstract: This is a report of a fortunate story of an unusual AK-47 bullet trajectory which took place during the Paris (France) attack of November 13 th, 2015. A young man, trying to protect his girlfriend, interfered between her and a shooter. He had been wounded in the posterior compartment of the thigh. The bullet penetrated him and, instead of exiting, rebound against his Smartphone, which was in the front pocket of his pants. Thanks to that, the missile bullet did not injure his girlfriend but ended its trajectory in the fat tissue of his thigh. O Thabouillot, P Perrier, NC Roche, D Agard, O Barbier, G Martin, E Viant, JB Leclere .A fortunate story of an unusual AK-47 bullet trajectory: always keep a Smartphone in your pocket .Prehosp Disaster Med, 2016 ;31 (3 ):343 –345 .